Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan di Hotel Adiwana Bisma Ubud - Dwitama, I Made Doni Priawan; Sulasmini, Ni Made Ayu; Apri, Ni Wayan Mega Sari (Jurnal Studi Perhotelan dan Pariwisata, 2024)
Purpose: This study aims to determine the effect of leadership style and work motivation on employee performance at Adiwana Bisma Hotel Ubud. Research methodology: This research was conducted in March-June 2022. The location of this research is the Adiwana Bisma Hotel, Ubud. Sang used in this study as many as 30 respondents. The data analysis techniques used in this research are Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F Test and t Test.Results: From the research results, it can be seen that leadership style has a significant positive effect on employee performance. Work motivation has a significant positive effect on employee performance. Leadership style and work motivation have a positive and significant effect on employee performance.Conclusions: This study shows that leadership style and work motivation have a positive and significant effect on employee performance at Adiwana Bisma Hotel Ubud. Improvements in leadership style and work motivation can directly improve employee performance. This confirms the important role of leadership and motivation in creating a productive work environment.Limitations: This study has limitations on the scope that is only focused on one hotel in the Ubud area, so the results may not necessarily be generalized to the hospitality industry at large. In addition, the variables studied were only limited to leadership style and work motivation. Contribution: This research contributes to human resource management, particularly in the hospitality industry. The findings serve as a reference for hotel managers in developing leadership strategies and motivation programs to boost employee productivity. Additionally, it can support internal decision-making and policy development to enhance overall organizational performance.Keywords: Leadership Style, Work Motivation and Employee PerformanceHow to Cite: Dwitama, I, M , D, P. Sulasmini, N, M, A. Apri, N, W, M, S. (2024). Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan di Hotel Adiwana Bisma Ubud. Jurnal Studi Perhotelan dan Pariwisata, 3(1), 1-10.